Millennium Awareness through Aceh History and Documentary Film (The Young Generation's Perspective Case Study) - Khalsiah Khalsiah; Saifuddin Yunus; Muthmainah Muthmainah (Budapest International Research and Critics University, 2022)
Culture and education History is a form of cultural heritage that must preserve. Various record-keeping methods are valuable lessons learned from previous figures or generations. Because of social changes, the millennial generation must influence the cultural environment in which they live. The research is to: a. Determine the level of millennial awareness and interest in history through documentary films and b. Determine the level of millennial awareness and interest in history through documentary films. And c. examining how millennials are now preserving history. Theoretically, to create knowledge treasures, especially in the social sciences. The qualitative research method study is scientific research, which prioritizes the process of deep between research participants to understand a phenomenon scientifically. Researchers will observe and interview respondents in various locations in Banda Aceh. The findings are expected to serve as a source of information and education for millennials about the history of the Aceh kingdom and provide teaching about Indonesian history via information technology. Furthermore, the study's findings are expected to benefit future researchers interested in this subject. The research will focus on how students in the millennial generation learn. The history of education must break out of its comfort zone at the descriptive narrative level. It can be developed in the millennial era using existing technology and historical science, built and re-miniatured into historical content that highlights production, theatre, creativity, and initiative.